STUDY ON THE DECLINE OF PERFORMANCE IN THE LONG JUMP TEST FROM THE PLACE DURING ONLINE SCHOOLING IN RURAL STUDENTS - Dulceanu, Corina; Herlo, Narcis Julien; Bulzan, Claudiu Octavian (Arena-Journal of Physical Activities, 2023)
In the field of school sports, emphasis has been placed on the use of general physical development exercises, due to their high degree of accessibility and the relative simplicity with which they can be transmitted to the student by the teacher, and mobility and local strength exercises, in order to prevent, or at least slowness, deterioration of students’ physical abilities . Our study is intended to make a statistical analysis of the results obtained by the students of the Sagu-Fiscut juetul Arad Middle School in two standing long jump tests, before and after the interruption of the face-to-face didactic activity. 94 rural students between the ages of 8 and 14 participated in the tests between 2020 and 2021. The goal is that practicing any kind of physical training, whether in person or online, will result in less change of the performance in a sports test than stopping any physical training. The final conclusion is that at present, the transition to an education system via the Internet is not a reliable approach.